2004
DOI: 10.1103/physrevlett.93.208302
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Low-Temperature Molecular Manipulation of Sexiphenyl Molecules on Ag(111) Using Scanning Tunneling Microscopy

Abstract: A novel scanning tunneling microscope manipulation scheme for a controlled molecular transport of weakly adsorbed molecules is demonstrated. Single sexiphenyl molecules adsorbed on a Ag(111) surface at 6 K are shot towards single silver atoms by excitation with the tip. To achieve atomically straight shooting paths, an electron resonator consisting of linear standing-wave fronts is constructed. The sexiphenyl manipulation signals reveal a pi ring flipping as the molecule moves from the hcp to fcc site. Ab init… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
66
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(68 citation statements)
references
References 22 publications
2
66
0
Order By: Relevance
“…97 Note however that in our case the topography signal never showed any typical signature for an adsorption of the adatoms on the tip, indicating a possible desorption of the adatoms or a tip-induced diffusion out of the scanning range. 98 Generally, the change in configuration referred in ͑ii͒ can also be understood from the arguments in ͑i͒. Change in the separation between two CAs or migration of two nonadjacent SV-type defects cannot be ruled out since CAs on the outer surface of small-diameter SWNTs and SVs have roughly the same mobility.…”
Section: H Defect Stabilitymentioning
confidence: 99%
“…97 Note however that in our case the topography signal never showed any typical signature for an adsorption of the adatoms on the tip, indicating a possible desorption of the adatoms or a tip-induced diffusion out of the scanning range. 98 Generally, the change in configuration referred in ͑ii͒ can also be understood from the arguments in ͑i͒. Change in the separation between two CAs or migration of two nonadjacent SV-type defects cannot be ruled out since CAs on the outer surface of small-diameter SWNTs and SVs have roughly the same mobility.…”
Section: H Defect Stabilitymentioning
confidence: 99%
“…A zigzag contour similar to the one we found here has been reported for sexiphenyl on Ag(111). 45,46 There, the authors showed that the edge of a phenyl ring appears bright if the center of the corresponding off-axis C-C bond is located on top of a silver surface atom; if the center of a C-C bond is positioned over a bridge site, the corresponding phenyl ring edge appears darker (Figure 4c). The similar alignment of sexiphenyl and NC-Ph 6 -CN in 〈1 j 10〉 implies that the aromatic backbone plays an important role for the epitaxy.…”
mentioning
confidence: 99%
“…For this purpose STM operating at He temperature (4 K) are usually employed for atom manipulation in order to insure a high stability of the system during the process. Larger systems such as organic molecules are easier to manipulate by STM than single atoms [68][69][70]72,73]. Stability is also enhanced by the fact that systems as organic molecules often include a couple of ligands moieties which allow the molecules to bind covalently to the metal surface onto which they are deposited [68,72,73].…”
Section: From Freely Suspended Wires To Single-wires Lifted By Stmmentioning
confidence: 99%
“…This dynamics is nowadays exploited to build and manipulate atomic-size devices on surfaces. A few examples are the assembly of atomic-size structures on a surface [57,58,[64][65][66] or the manipulation of mesoscopic systems such as organic molecules [67][68][69][70][71][72][73]. The high stability and reproducibility of STM in manipulating adsorbates deposited on a surface is of fundamental importance to understand transport characteristics in view of future applications in functional nanoscale devices.…”
Section: From Freely Suspended Wires To Single-wires Lifted By Stmmentioning
confidence: 99%
See 1 more Smart Citation